2011
DOI: 10.1371/journal.pone.0023423
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy-Induced miR-21 Promotes Axon Growth in Adult Dorsal Root Ganglion Neurons

Abstract: Following injury, dorsal root ganglion (DRG) neurons undergo transcriptional changes so as to adopt phenotypic changes that promote cell survival and axonal regeneration. Here we used a microarray approach to profile changes in a population of small noncoding RNAs known as microRNAs (miRNAs) in the L4 and L5 DRG following sciatic nerve transection. Results showed that 20 miRNA transcripts displayed a significant change in expression levels, with 8 miRNAs transcripts being altered by more than 1.5-fold. Using q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
152
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(167 citation statements)
references
References 47 publications
13
152
0
Order By: Relevance
“…2B). These results are in line with a recent genetic profiling study in which miR-138 was among a group of microRNAs that are down-regulated in DRGs after peripheral nerve injury (Strickland et al 2011). To determine the functional role of miR-138 in axon regeneration, we used a recently developed cellreplating model (Saijilafu and Zhou 2012).…”
Section: Down-regulation Of Mir-138 After Axotomy Is Necessary For Resupporting
confidence: 81%
See 2 more Smart Citations
“…2B). These results are in line with a recent genetic profiling study in which miR-138 was among a group of microRNAs that are down-regulated in DRGs after peripheral nerve injury (Strickland et al 2011). To determine the functional role of miR-138 in axon regeneration, we used a recently developed cellreplating model (Saijilafu and Zhou 2012).…”
Section: Down-regulation Of Mir-138 After Axotomy Is Necessary For Resupporting
confidence: 81%
“…Several previous studies have shown that miR-34a can target SIRT1 in different tissues (Yamakuchi 2012). However, the expression of miR-34a does not seem to be altered in adult sensory neurons upon peripheral axotomy (Strickland et al 2011;Zhang et al 2011;Zhou et al 2011), suggesting that it is unlikely to target SIRT1, which is up-regulated drastically upon axotomy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding strongly suggests the involvement of miRNAs in long-term cortical plasticity following esophageal acid exposure early in life. Here, we review specific miRNAs that have been identified as the regulators of nociceptive activity and highlight their possible association with pain processing in various pain conditions (Table 87, 99,100,101,103,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] ).…”
Section: Icrornas In Visceral Painmentioning
confidence: 99%
“…Taxol has also proven to stimulate axonal regeneration in models of spinal and optic nerve injury [51,52]. promotes axon growth in adult dorsal root ganglion neurons [63]. Among the microRNAs, that are upregulated in dorsal root ganglia after nerve injury, miR-222 was identified and found to target PTEN [64], suggesting that the injuryresponse disengages inhibitory mechanisms to stimulate regeneration in the PNS, which could be useful in designing therapies for CNS injuries.…”
Section: Overview Over Intrinsic Regulation Of Axon Growth and Regenementioning
confidence: 99%